Resource curse in oil exporting countries - Kakanov, Evgeny (OECD Economics Department Working Papers, 2018)
This paper provides a comprehensive analysis of the "resource curse" phenomenon, i.e. the negative impact of the natural resource abundance on the long-term economic development, for a set of oil exporting countries. It distinguishes between two potential drivers of the resource curse: oil dependence and oil price shocks, and it investigates whether the resource curse depends on a country's institutional and macroeconomic environment. The empirical analysis relies on a panel of 24 oil exporters between 1982 and 2012 and an error correction model. The paper provides robust evidence in favour of the resource curse hypothesis: a 10-percentage point increase in the oil export share is associated with a 7% lower GDP per capita in the long run. Oil price shocks appear to have an asymmetric impact in the short run: the growth effect is positive when oil prices rise, while no statistically significant effect is observed when they fall. There is an indirect evidence that the impact of an oil price shock is partly offset by fiscal policies, particularly in countries with high oil dependence. In the long run, an oil price shock does not appear to have a statistically significant impact on GDP. Finally, exchange rate regimes seem to play a role: a fixed exchange rate regime is associated with a higher GDP, potentially due to the presence of sovereign wealth or stabilisation funds. Most of oil exporters with a fixed exchange rate regime have such funds allowing them to actively use fiscal policies to counter oil price shocks